Intercultural Communication Competence through Experiential (GIST – Education and Learning Research Journal, 2007)
Approaches to intercultural communication competence (ICC) generally argue the need for objective knowledge about another culture as well as knowledge about and the ability to achieve appropriate behaviors of that target culture. Most of these approaches continue to base themselves on a conception of culture as comprehensive but static. Intercultural contact in this sense is a matter of contrasting and overcoming differences between one’s own culture and the host or target culture. Other approaches, however, are adopting a more multicultural and pluricultural view of intercultural competence, and a more fluid and dynamic conceptualization of culture. These approaches tend to see the intercultural dynamic as an opportunity for “third places” to emerge where entirely new cultural knowledge and behavior can be constructed through cross-cultural contact and the interaction process in itself. This view sees cultures not as fixed entities to be learned and then copied, but rather as a hybrid and emergent phenomenon of today’s societies. What are needed, it is argued, are individuals who are more aware of their own linguaculture in a much deeper way, and who are open to exploring new identities and perspectives as part of their daily contact with others. Here, the other is not only the different culture, with the emphasis on “different,” but rather the other may be anyone with whom the individual chooses to interact. This paper explores the Subculture Adaptation Project conducted with third semester students in the bilingual education program at the Institución Universitaria Colombo Americana. Students were asked to choose a subculture to which they wanted to or needed to belong, and complete a series of tasks to document the adaptation process. This exercise reveals that students who achieved the greatest degree of adaptation were those who were not limited to focusing on differences between themselves and members of the subculture. Rather, these students consistently sought out emergent third places where they could construct relationships and interactions that brought together self and other in dialogic encounters where new understandings, relationships and identities could emerge.